2011
DOI: 10.4238/vol10-3gmr1156
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei as biomarkers for evaluating the risk of malignant transformation in the uterine cervix

Abstract: ABSTRACT. We evaluated micronucleus and apoptosis occurrence among women with normal smears and women with different kinds of cervical abnormalities, i.e., inflammatory processes and low-and high-grade squamous intraepithelial lesions (N = 12, N = 10 and N = 27, respectively). The sample included 59 women who were seen at a public medical service for cervical cancer prevention in Feira de Santana, Bahia, Brazil. The diagnosis was established by means of cytological, colposcopic, and histopathological examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
2
13
1
Order By: Relevance
“…Minimal values were reported by Aires et al [17] (0.15‰) (3-fold higher than the value found by Safi Oz et al) and the maximal value by Chakrabarti and Dutta [18] (4.9‰ in postmenopausal women, 98-fold higher than the value found by Safi Oz et al). It is noteworthy that the last authors found 1.9‰ cells with MN in premenopausal women.…”
contrasting
confidence: 40%
“…Minimal values were reported by Aires et al [17] (0.15‰) (3-fold higher than the value found by Safi Oz et al) and the maximal value by Chakrabarti and Dutta [18] (4.9‰ in postmenopausal women, 98-fold higher than the value found by Safi Oz et al). It is noteworthy that the last authors found 1.9‰ cells with MN in premenopausal women.…”
contrasting
confidence: 40%
“…Analysis of MN in interphasic cells of cell smears has been used to detect chromosomal alterations that arise due to the aneugenic and clastogenic effects caused by a variety of compounds. It is being used in the analysis of exfoliated cells to detect precancerous and cancerous lesions, determining high-risk groups for tumors in the oral cavity, urinary tract (bladder), cervix, and esophagus [37,38]. The frequency of micronucleated cells increases in tissues exposed to carcinogens before any clinical symptom emerges.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, false negatives account for 10–50% of Pap test results (Dehner, 1993). Complementary methods aimed at increasing the sensitivity of screening for cervical cancer have been described, including high-risk HPV testing (Abreu et al , 2012) and micronucleus (MN) identification (Aires et al , 2011; Gayathri et al , 2012). Although HPV testing is considered the gold standard for diagnosing this viral infection and has the potential to improve the effectiveness of screening programs, its implementation must still be kept low-cost in order to be used in low-income populations (Abreu et al , 2012).…”
mentioning
confidence: 99%